Downregulation of PLIN2 in human dermal fibroblasts impairs mitochondrial function in an age‐dependent fashion and induces cell senescence via GDF15 - Chiariello, Antonio; Rossetti, Luca; Valente, Sabrina; Pasquinelli, Gianandrea; Sollazzo, Manuela; Iommarini, Luisa; Porcelli, Anna Maria; Tognocchi, Monica; Conte, Giuseppe; Santoro, Aurelia; Kwiatkowska, Katarzyna M.; Garagnani, Paolo; et al. (Aging cell, 2024)
Perilipin 2 (PLIN2) is a lipid droplet (LD)‐coating protein playing important roles in lipid homeostasis and suppression of lipotoxicity in different tissues and cell types. Recently, a role for PLIN2 in supporting mitochondrial function has emerged. PLIN2 dysregulation is involved in many metabolic disorders and age‐related diseases. However, the exact consequences of PLIN2 dysregulation are not yet completely understood. In this study, we knocked down (KD) PLIN2 in primary human dermal fibroblasts (hDFs) from young (mean age 29 years) and old (mean age 71 years) healthy donors. We have found that PLIN2 KD caused a decline of mitochondrial function only in hDFs from young donors, while mitochondria of hDFs from old donors (that are already partially impaired) did not significantly worsen upon PLIN2 KD. This mitochondrial impairment is associated with the increased expression of the stress‐related mitokine growth differentiation factor 15 (GDF15) and the induction of cell senescence. Interestingly, the simultaneous KD of PLIN2 and GDF15 abrogated the induction of cell senescence, suggesting that the increase in GDF15 is the mediator of this phenomenon. Moreover, GDF15 KD caused a profound alteration of gene expression, as observed by RNA‐Seq analysis. After a more stringent analysis, this alteration remained statistically significant only in hDFs from young subjects, further supporting the idea that cells from old and young donors react differently when undergoing manipulation of either PLIN2 or GDF15 genes, with the latter being likely a downstream mediator of the former. Perilipin 2 (PLIN2) plays a role in supporting a normal mitochondrial functionality. We showed that PLIN2 knockdown (KD) in human dermal fibroblasts caused a decline of mitochondrial function, an increased expression of the stress‐related mitokine GDF15 and the induction of cell senescence. Interestingly, the GDF15 KD abrogated the induction of PLIN2 KD‐associated cell senescence, suggesting that GDF15 could be the mediator of this phenomenon.